PENGARUH PERHATIAN DAN MOTIVASI ORANG TUA TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS IV SEKOLAH DASAR - Maria Desinta; Asrori Asrori; Antonius Totok Priyadi; Tomo Djudin; Endang Purwaningsih (STKIP Persada Khatulistiwa Sintang, 2023)
This research aims to determine the influence of parental attention and motivation on the mathematics learning achievement of grade IV students at SD Suster Pontianak. The research was carried out using a quantitative approach, in the form of a comparative study. The population in this study was 105 grade IV students at Suster Singkawang Elementary School with a sample of 32 students. The data collection tool used was a questionnaire to determine parental attention and motivation, as well as report cards for mathematics subjects. Based on data analysis, it was found that parental attention received a score with an average of 77.4 in the medium category, parental motivation received an average score of 64.2 in the medium category and student learning achievement with an average of 79.3 in the medium category; parental attention and parental motivation partially influence the learning achievement of fourth grade students at the Pontianak Sisters Private Elementary School; and parental attention and parental motivation simultaneously influence the learning achievement of fourth grade students at the Pontianak Sister Private Elementary School as proven by the results of ANOVA analysis with a significance of 0.000 <0.05. It can be concluded that parental attention and motivation have an influence on the mathematics learning achievement of grade IV students at Suster Pontianak Elementary School.